Linial's Dual Conjecture for Path-Spine Digraphs - Carvalho, Vinícius de Souza; da Silva, Cândida Nunes; Lee, Orlando (Anais do Encontro de Teoria da Computação (ETC), 2020)
Given a digraph D, a coloring  𝒞  of D is a partition of V(D) into stable sets. The k-norm of  𝒞  is defined as ΣC∈𝒞 min{|C|, k}. A coloring of D with minimum k-norm has its k-norm noted by χk(D). A (path)-k-pack of a digraph D is a set of k vertex-disjoint (directed) paths of D. The weight of a k-pack is the number of vertices covered by the k-pack. We denote by λk(D) the weight of a maximum k-pack. Linial conjectured that χk(D) ≤ λk(D) for every digraph. Such conjecture remains open, but has been proved for some classes of digraphs. We prove the conjecture for path-spine digraphs, defined as follows. A digraph D is path-spine if there exists a partition {X, Y} of V(D) such that D[X] has a Hamilton path and every arc in D[Y] belongs to a single path Q.